2021
DOI: 10.20463/pan.2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activities of Sargassum horneri extract in RAW264.7 macrophages

Abstract: [Purpose] In this study, we investigated whether a 70% ethanolic (EtOH) extract of Sargassum horneri had antioxidant and anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated macrophage-like RAW 264.7 cells.[Methods] The proximate composition, fatty acids, amino acids, and dietary fiber of S. horneri, various biologically active compounds, and antioxidant activity were analyzed.[Results] The DPPH and ABTS free radical scavenging activities, as well as the reduction power, of the S. horneri extract u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, there is increasing evidence that inhibition of TNF-α can be an option for the treatment of eye diseases (34). However, TNF-α inhibitors can have systemic side effects that are related to malignancy, serious infections, retinal vein occlusion (RVO), inflammation, and demyelination (35)(36)(37), and numerous attempts have been made to evaluate their anti-inflammatory effects as a functional ingredient of natural substances that were previously determined to be safe and easy to use (38)(39)(40). In our study, we found that TNF-α stimulation led to the upregulation of IL-6, IL-1ß, IL-8, and TNF-α, while treatment with AB_SH and fucoidan inhibited mRNA and cytokine production in AREP-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is increasing evidence that inhibition of TNF-α can be an option for the treatment of eye diseases (34). However, TNF-α inhibitors can have systemic side effects that are related to malignancy, serious infections, retinal vein occlusion (RVO), inflammation, and demyelination (35)(36)(37), and numerous attempts have been made to evaluate their anti-inflammatory effects as a functional ingredient of natural substances that were previously determined to be safe and easy to use (38)(39)(40). In our study, we found that TNF-α stimulation led to the upregulation of IL-6, IL-1ß, IL-8, and TNF-α, while treatment with AB_SH and fucoidan inhibited mRNA and cytokine production in AREP-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The S. horneri component has been shown to exert suppressive effects on the inflammatory state of various cell types, including macrophages, retinal cells, and dermal fibroblasts [39][40][41][42][43][44][45][46][47][48][49][50][51]. In this mini review, the author has focused on inflammatory macrophages.…”
Section: Suppressive Effects Of the S Horneri Component On The Inflam...mentioning
confidence: 99%
“…In this mini review, the author has focused on inflammatory macrophages. The S. horneri component with 70% EtOH extracts, such as phenolics and flavonoids, has been shown to have excellent anti-inflammatory and antioxidant activities [39]. Levels of several cytokines, including prostaglandin E2 (PGE2), TNF-α, and interleukin (IL)-6, which mediate pro-inflammatory effects, were found to be reduced by treatment with S. horneri extract [39].…”
Section: Suppressive Effects Of the S Horneri Component On The Inflam...mentioning
confidence: 99%
See 1 more Smart Citation
“…피부의 탄력과 주름을 개선하고 진피층의 섬유아세포를 활성화 시키는 식품의약품안전처 고시 원료로는 레티놀(retinol), 레티닐 팔미테이트(retinylpalmitate), 아데노신(adenosine) 등의 원료들 이 있으며, 이들 원료를 함유한 제품들이 주름개선의 효과를 보인 다 (Chan et al, 2006;Sorg et al, 2006) (See et al, 1998;Halliwell & Gutteridge, 1999;Nagayama et al, 2002) (Zhu et al, 2003;Zhu et al, 2004;Zhu et al, 2006;Kim et al, 2017;Kim, 2021a;Kim et al, 2021b). 모자반과에 속한 다른 종류의 모자반인 큰열매모자 반(Sargassum macrocarpum) 추출물과 짝잎모자반(Sargassum hemiphyllum)은 항산화효과 및 세포 활성을 강화하는 효과가 보고 된 바있으며, 꽈배기모자반(Sargassum siliquanstrum)은 항염효 과가 보고된 바 있다 (Lee et al, 2016;Kim, 2021a;Kim et al, 2021b ). 피부질환이 발생하게 된다 (Talwar et al, 1995;Kim et al, 2011).…”
Section: Introductionunclassified